ANALISIS MOTIVASI DAN KEPUASAN KERJA TERHADAP PRODUKTIVITAS KERJA GURU SMKS KATOLIK KEFAMENANU-TIMOR TENGAH UTARA - Lao, Hendrik A.E.; Leobisa, Jonathan (Jurnal Dedikasi Pendidikan, 2022)
The work carried out must be based on high work motivation and supported by balanced job satisfaction so that it has an impact on maximum work productivity. The aims of this study are 1) to determine the effect of work motivation on teacher work productivity; 2) to determine the effect of job satisfaction on teacher work productivity. The research method used is a quantitative method with questionnaires and documentation data collection techniques, while the data analysis technique uses multiple linear regression analysis with the help of SPSS 23. Research findings are: 1) has a fairly significant effect of motivation on work productivity of 41.4 % > 5% which means Ho is rejected and Ha is accepted. So that the contribution of motivation to work productivity is quite influential; 2) has a significant effect of job satisfaction on work productivity of 70.05% > 5%, which means Ho is rejected and Ha is accepted. So that the contribution of satisfaction to work productivity has a good effect. The conclusion is that motivation and job satisfaction need to be increased in order to achieve high productivity from teachers at the Kefamenanu Catholic Vocational School.